The Neonatal Comfort Care Program: Origin and Growth Over 10 Years - Wool, Charlotte; Parravicini, Elvira (Frontiers in Pediatrics, 2020)
The objective of perinatal palliative care is to provide holistic and comprehensive health care services to women who are anticipating birth of a neonate diagnosed prenatally with a life-limiting condition, and to continue supportive interventions for the mother and neonate after the birth. The nature of pregnancy, with two patients requiring medical care, requires clinicians from different specialties to engage with one another, the patient, and her chosen family members. Following birth, additional skill sets to treat the medical and comfort needs of the neonate, as well as the psychoemotional and medical needs of the mother, are required. An interdisciplinary team is necessary to assist families throughout the pregnancy and postnatal journey, and coordination of such care is an integral component of palliative care services. The number of palliative care programs is increasing, but little is written about the origins of such programs, their subsequent growth, and how transitions of care occur within the programs. In this publication we will present data garnered from interdisciplinary team members of a single organization, the Neonatal Comfort Care Program at Columbia University Irving Medical Center, and how they provide care for families throughout the pregnancy and postnatal trajectory. We will address the origin and growth of the program, the development of the interdisciplinary team, and the strategies used for high-quality communication and their respective impact on care continuity. We will provide specific recommendations from data gathered from team members, examine the role of formal and informal education, and identify barriers and future opportunities.